Development and prevalence of castration-resistant prostate cancer subtypes - Vellky, Jordan E.; Ricke, William A. (Neoplasia (New York, N.Y.), 2020)
Castration-resistant prostate cancer (CRPC) occurs when prostate cancer (CaP) progresses under therapy-induced castrate conditions. Several mechanisms have been proposed to explain this acquired resistance, many of which are driven by androgen receptor (AR). Recent findings, however, sub-classified CRPC by downregulation/absence of AR in certain subtypes that consequently do not respond to anti-androgen therapies. To highlight the significance of CRPC sub-classification, we reviewed the development and treatment of CRPC, AR downregulation in CRPC, and summarized recent reports on the prevalence of CRPC subtypes. Using a medline-based literature search, we reviewed mechanisms of CRPC development, current treatment schemes, and assessed the prevalence of AR low/negative subtypes of CRPC. Additionally, we performed immunohistochemical staining on human CRPC specimens to quantify AR expression across CRPC subtypes. In the majority of cases, CRPC continues to rely on AR signaling, which can be augmented in castrate-conditions through a variety of mechanisms. However, recently low/negative AR expression patterns were identified in a significant proportion of patient samples from a multitude of independent studies. In these AR low/negative cases, we postulated that AR protein may be downregulated by (1) promoter methylation, (2) transcriptional regulation, (3) post-transcriptional regulation by microRNA or RNA-binding-proteins, or (4) post-translational ubiquitination-mediated degradation. Here, we discussed mechanisms of CRPC development and summarized the overall prevalence of CRPC subtypes; interestingly, AR low/negative CRPC represented a considerable proportion of diagnoses. Because these subtypes cannot be effectively treated with AR-targeted therapeutics, a better understanding of AR low/negative subtypes could lead to better treatment strategies and increased survival.